167k views
1 vote
Find (f/g) (x) for the functions provided: ƒ(x) = x3 − 27, g(x) = 3x − 9

User Eivanov
by
5.1k points

2 Answers

4 votes

Answer:

Explanation:

User Phyx
by
4.6k points
4 votes

Answer:


((f)/(g))(x)=(1)/(3)(x^2+3x+9)

Explanation:

We have been given that


f(x)=x^3-27,g(x)=3x-9

We can use the formula for difference of cubes to simplify the function f(x)

difference of cubes -
a^3-b^3=(a-b)(a^2+ab+b^2)


f(x)=x^3-27\\\\=x^3-3^3\\\\=(x-3)(x^2+3x+9)

And g(x) can be written as


g(x)=3x-9\\=3(x-3)

Thus, we have


((f)/(g))(x)=((x-3)(x^2+3x+9))/(3(x-3)

On cancelling the common factors, we get


((f)/(g))(x)=(1)/(3)(x^2+3x+9)

User Selcuk Akbas
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.